THE EFFECT OF GOAT LIQUID FERTILIZER AND SOIL ON PLANT GROWTH AND YIELD Asystasia gangetica (L.) subsp. Micrantha - I. P. B. R. A., Pranata; Duarsa, M. A. P.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika; Vol 11 No 3 (2023): Vol. 11 No. 3 Tahun 2023; September - December, 2023)
This study aims to determine the effect of goat dung liquid fertilizer and soil type on the growth and yield of Asystasia gangetica. This research was conducted in a greenhouse, Jalan Raya Sading number 93, Mengwi, Badung, Bali. The study lasted for three months from preparation to cutting. The study used a completely randomized split plot design with two factors. The first factor is the main plot, namely the type of soil consisting of Sobangan soil (TL), Pengotan soil (TR) and Jimbaran soil (TM). The second factor in the subplot/subplot is goat manure liquid fertilizer consisting of untreated goat manure (P1), goat manure + EM 4 (P2), goat manure + EM 4 + chopped corn waste (P3). There were nine treatment combinations and each treatment was repeated four times so that there were 36 experimental units. The variables observed were growth variables, yield variables and plant growth characteristics variables. The results showed that there was an interaction between leaf dry weight and stem dry weight for leaf area per pot. The combination of TM and P2 fertilizer produced the highest value of 1,87 g in the ratio of leaf dry weight to stem dry weight, while the highest combined leaf area per pot was found in TRP1 with a value of 366,24 cm. In the growth and yield of Asystasia gangetica, the use of Pengotan (TR) soil type got optimal results, while the P1 and P3 fertilizer types also produced an average result that was not much different for the growth and yield of Asystasia gangetica plants. Keywords: Asystasia gangetica, type of soil, goat liquid fertilizer